Basal cell skin cancer with metastasis to subcutaneous fat—a case report - Veronika Rumyantseva; Anna Sukhotko; Victor Sukharev; Anna Bumbu; Evghenii Zakurdaev; Serghei Covantsev (Frontiers in Surgery)
Basal cell carcinoma (BCC) is a malignant neoplasm of the skin that originates from the cells of the basal layer of the epidermis and is the most common skin cancer worldwide, accounting for more than 75% of all nonmelanoma skin cancers. About 4 million BCCs are diagnosed annually worldwide. Despite being the most common skin tumor, metastasis is rare and occurs in 0.0028%–0.55% of cases. In this case report, we present a rare case of giant basal cell carcinoma with metastasis to the subcutaneous fat in a 69-year-old woman.